Parental Rearing Patterns and Interpersonal Skills in Deaf Chinese College Students: The Mediating Role of Theory of Mind - Wu, Yang; Liu, Xiping; Zhang, Shengnan; Zhong, Rubo (Frontiers in Psychology, 2021)
This study examined the associations between parental rearing patterns and interpersonal skills via the mediation of Theory of Mind (ToM) in a sample of 369 deaf Chinese college students. The results showed that negative parental rearing patterns was directly and negatively associated with interpersonal skills, and positive parental rearing patterns was directly and positively associated with interpersonal skills. There were also indirectly associated with interpersonal skills via ToM. We also considered whether the mediation of ToM was different for male participants and female participants. The indirect associations between parental rearing patterns and interpersonal skills via ToM existed for female participants, but not for male participants. These results indicated that deaf college students’ perceived parental rearing patterns are associated with their interpersonal skills, and parents of deaf children should incorporate ToM in their everyday rearing patterns to improve their children’s interpersonal skills, especially for girls.